The Terminology as A Linguistic Phenomenon - Pardayeva Sojida Ahmatovna (Genius Journals, 2022)
In this article, as there are changes in every field as a result of economic changes, there is also development in the field of insurance. In modern linguistics, extensive research is being conducted by specialists in order to study the formation, development and peculiarities of certain terminological systems in different system languages. Nevertheless, controversial issues in terminology have not yet lost their relevance and are currently awaiting resolution. In this sense, the various innovations that have taken place around the concept of the term, the developed scientific-theoretical views and research results have attracted not only linguists, but also insurance professionals and remain one of the most pressing issues.
Keywords: Insurance; linguistics; terminology; complex term